Есть ответ 👍

Выражение (5-m^4)(25+m^4+5m^8)-5(5-m^6)^2

255
410
Посмотреть ответы 2

Ответы на вопрос:

Diannata
4,7(69 оценок)

Уменя такой ответ получился (5-m^4)(25+m^4+5m^8)-5(5-m^6)^2= =5*25+5*m^4+5*5m^8-m^4*25-m^4*m^4-m^4*5m^8-5(5^2-2*5*m^6+(m^6)^2)= =75+5m^4+25m^8-25m^4-m^8-5m^12-5*25+5*10m^6-5*m^12= =75-75+5m^4-25m^4+50m^6+25m^8-m^8-5m^12-5m^12= =-20m^4+50m^6+24m^8-10m^12= =2m^4(-10+25m^2+12m^4-5m^8)
basarabbozya
4,5(30 оценок)

ответ:

1) більша діагональ 10см

2) 3×5=15см квадратних

Популярно: Алгебра